The title of the research: The effect of separation and the repercussions of memory in the language of the poet Jamil bin Muammar Al-Adhari. (selected models) - ابراهيم نغم; عدنان محمد أحمد; رباح علي (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
Jameel’s artistic speech, which spoke about separation and the repercussions of the memory of the beloved within himself, was based on a consistent structure. It is the structure of fission and rupture. This became clear by interrogating the meanings of the verses at the linguistic or formal level, and studying the relationships of the functions used with each other. The analytical study showed that the hadith of separation and the hadith of remembrance form a cohesive artistic unit, supported by its words, structures, and images. To suggest the significance of the poet’s self being torn apart, exhausted by love, and her division between what she desires and what she is unable to achieve. The confluence of the meanings of these styles and the words used to express them in a single structure is nothing but confirmation of the consistency of the poetic discourse artistically, and its integration in a way that indicates a poetic and emotional experience that is worth reading after reading.